Genetic Parameters for Cow-calve Phase in Hereford x Angus Crosses Under Extensive Grazing - Pereyra, Fernando; Urioste, Jorge Ignacio; Gimeno, Diego; Peñagaricano, Francisco; Bentancur, Dorrel; Espasandín, Ana (Agrociencia Uruguay, 2015)
In a diallelic experiment between Hereford (H/H) and Aberdeen Angus (A/A) breed, developed between 1994 and 2002 at the Bernardo Rosengurtt Experimental Station (College of Agriculture-University of the Republic, Uruguay) individual (giA-giH) and maternal (gmA-gmH) breed differences, individual (hiAH) and maternal (hmAH) heterosis were estimated, using linear models for body condition at calving (BCC), birth weight (BW), and weaning weight (WW), and generalized linear models for weaning percentage (% W). Racial and estimated heterosis effects were not significant for BCC, while for BW the difference in kg was negative, and H/H was superior (-1.18 ± 0.42 kg, P = 0.0051). For WW, the difference between maternal effects (gmA - gmH) was positive, with 4.87 ± 1.01 kg (P <0.0001), and individual heterosis was 5.12 ± 1.24 kg (P <0.0001). The hiAH for % W was 0.22 ± 0.03. The hmAH was significant for WW (11.58 ± 1.48 kg, P=0.0001). At birth, calves H/H, A/H and H/A were heavier than A/A. For % W, crossbred dams averaged 24.7 points (14.9 %) higher than pure breeds (85.0 vs. 60.3). Crossbred breed dams weaned calves significantly heavier (means 159.1 kg). Hereford dams weaned significantly lighter calves (means 143.3kg); while the calves of Angus dams weighed 151.6 kg.